Why There Are Certain Parallels Between Joachim C. Fest’s Hitler-Biography and Michael Wolff’s Trump-Book - Christian Fuchs (tripleC: Communication, Capitalism & Critique)
Joachim C. Fest published one of the most widely read Hitler biographies in 1973. Are there parallels of its analytical approach to Michael Wolff’s “Fire and Fury: Inside the Trump White House”?